Pensamiento crítico entre hombres y mujeres del quinto grado secundaria en la Institución Educativa Mariscal Oscar Raymundo Benavides, Iquitos 2021 - Tangoa Malafaya, Karel (2025)
The purpose of the research was to explore possible differences in critical thinking among fifth-grade secondary school students, according to gender, at the Mariscal Oscar Raymundo Benavides school in Iquitos, 2021. A quantitative, basic, comparative methodology was used, consisting of administering a questionnaire to 225 students in the study sample. The results obtained using the Student's t-test revealed that the level of critical thinking differs significantly between male and female students, with a p-value of 0.01 and a significance threshold of 0.05. The inferential analysis of the dimensions of critical thinking using the Student's t-test revealed that there is a notable distinction in the first dimension, referring to analytical ability, in terms of the level of critical thinking by gender of the students. This is evidenced by a p-value of 0.01, which is lower than the established statistical decision threshold (0.05). Statistical analysis using the Mann-Whitney U test revealed significant differences in the level of critical thinking in the second dimension, the ability to infer (with a p-value of 0.002, which is less than 0.05). The consistency of the results was also reflected in the third, fourth, fifth, and sixth dimensions, related to the ability to explain (p-value of 0.001); interpret (p-value of 0.001); evaluate (p-value of 0.002), and self-regulation, a significant difference in critical thinking was found according to the student's gender (p-value of 0.003).